Motives, benefits, and challenges of Higher Education expansion in China - Jasmin Omary Chunga; Ayubu Ismail Ngao (Center for Humanities and Innovation Studies, 2021)
China believes in education as an investment of human capital for future returns. It has been a long-time desire for the Chinese government to expand and invest in higher education. The leadership of Deng Xiaoping inspired Chinese people about education it should be open over the world, for the future, and towards modernization. The purpose of higher education in global views is to promote the development of a nation in political, economic, technical, and social spheres. There are gradual changes in higher education after the open policy in China, which influences the expansion of higher education institutions. Higher education acts as a tunnel to prepare several professionals and talents, which will be helpful to the social changes in science and social science programs. Global competence leads the Chinese government to expand higher education in enrollment rate and improves the quality of higher education in acquiring competent knowledge that copes with the global market. This paper focused on reviewing literary works on motives, benefits, and challenges of higher education expansion in China through reviewing different studies from local and international perspectives. From compulsory through higher education, the curriculum should place a greater emphasis on competency. To deal with the wind of unemployment caused by the rise of higher education in China, the government should encourage and support graduates to find innovative and creative skills. For China's economy to grow quicker, a well-educated society requires graduates to apply their skills to solve many societal problems.